Late onset startle induced tics. Issue 6 (1st December 1999) - Tijssen, M A J; Brown, P; Morris, H R; Lees, A
Abstract : Three cases of late onset Gilles de la Tourette's syndrome are presented. The motor tics were mainly induced by an unexpected startling stimulus, but the startle reflex was not exaggerated. The tics developed after physical trauma or a period of undue emotional stress. Reflex tics may occur in Gilles de la Tourette's syndrome, but have not been described in late onset Tourette's syndrome. Such tics must be distinguished from psychogenic myoclonus and the culture bound startle syndromes.